THE INNOVATIONS’ MONITORING IN THE DEVELOPED ECONOMIES: THE SYSTEMS OF INDICATORS AND THEIR APPLICATION IN RUSSIA - N. M. Abdikeev (Real Economics Publishing House, 2019)
Relevance. Further to the postindustrial transition and the Forth Industrial revolution challenges operating nowadays in the world the Russian federation leaders task the nation to provide intensive innovation development of the economy and society with the effective administration of the process. The fulfillment requires toapply to such a praxis in the developed economies with the advanced manufacturing. Research object. The paper provides the analysis of the innovative activity indicators systems of the three developed economies leading in the world for a long time in manufacturing as well as in the novelties production and commercialization spheres, i.e. USA, Japan and Germany. Herewith the main principles of the systems’ formulation, bases to select their particular indicators has been determined, the element composition analyzed and their structures compared. Methods. To solve the task various research instruments have been applied: the system analysis, the content analysis, the comparative one and others. The institutional and evolutional theories and the modern political-economic approaches constituted the methodological basis of the research. Results. The operation of the research facilitated the determination of the perspective approaches to form the systems of innovation activity indicators there to be applied and?\?or adapted in Russia and the recommendation to make use of these. The comparative analysis realized manifested different variants of the system’ structures with such bases and facilitated the elaboration their typology further to the modes of the indicators’ grouping, their factors of influence and the presence?\?absence of the synthesizing indicator. The conclusions served for the recommendations to use some principles and methods of the foreign systems of innovation activity indicators’ constitution. Prospects. The immediate perspective of the research realized if the practical application of the deductions made, the theoretical conceptualization of the results obtained and the determination of the opportunities the systems to refine further on.